Avaliação eletrofisiológica da ação da (+) - catequina em um modelo animal de isquemia cerebral - Cabral, Francisco Romero (2001)
In the present work we tried to demonstrate a possible citoprotective activity of three different doses of (+)-catechin (0.5, 2.5 and 5.0mg), studying the cerebral electric activity after ischaemia induced by common carotid arteries bilateral obliteration of urethane anaesthetized Wistar rats. The electroencephalographic waves were recorded from subcutaneous electrodes on left frontal (F3), right frontal (F4), left parietal (P3), right parietal (P4) and vertex (Cz) regions. The electrophysiological analysis consisted of the absolute amplitude means evaluation of the several frequency spectra (alpha, betai, beta2, betas, theta and delta). An appropriate hardware and software was used to analyze the cerebral electric activity. We verified a significant increase (p<0,05) of the absolute amplitude means of the several spectra frequencies evaluated after obiiteration of both common carotid arteries and infusion of the three different doses of (+)-catechin solution. The left intracarotid infusion of 0.5 and 2.5 mg of(+)-catechin in rats caused a non-homogenous increase of the absolute amplitude means of the EEG spectra frequencies. However, the dose of 5.0 mg of (+)-catechin promoted a constant amplification in all of the absolute amplitude means of the EEG spectra frequencies. We concluded that the method used in this work is adequate to study citoprotective substances for the rat central nervous system and that (+)-catechin exerted a citoprotective effect in cerebral ischaemic rats induced by common carotid arteries biiatera! obiiteration.